Status Perkawinan dan Pengeluaran Konsumsi Bukan Pangan bagi Perempuan - Resti Maheralia; I Dewa Gede Karma Wisana (Mahesa Research Center, 2022)
This article aims to analyze the comparison of economic well-being between women experiencing a marital dissolution and married women on non-food consumption expenditures. The research question is focused on a marital dissolution (separated, divorced, or widowed) which always harms women. Some empirical studies find that women with discontinuous marriage (divorced or widowed) have lower economic well-being than married ones. To analyze the aforementioned research question, this article applied income pooling concept and employed fixed effects regression. Data in this study used Indonesian Family Life Survey (IFLS) 2007 and 2014. Results suggested that women experiencing a marital dissolution had a greater expenditure compared to married ones. However, this does not imply that the prior group has better economic well-being than the latter one. The marital dissolution incident causes women to manage a numerousadjustments in overcoming difficulties that arise after such incident. The decomposition of non-food consumption expenditures show that some of the items are used to recover after such incident.